2008
DOI: 10.1510/icvts.2008.178111
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted cervical mediastinoscopy: our seven-year experience

Abstract: Mediastinal exploration is a common procedure used for the diagnosis of the thoracic diseases and the staging of lung cancer. A retrospective review was performed to assess sensitivity, specificity, accuracy and morbidity of video-assisted cervical mediastinoscopy (VACM). From 1999 to 2006 a total of 139 VACMs were performed in 138 patients. Eighty-seven patients were evaluated for known or suspected lung cancer (CN2 or CT scan)--group 1. Fifty-one patients underwent VACM for the evaluation of adenopathies or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…A diagnosis of sarcoidosis with conventional TBNA has been reported in 48%–82% of the cases, which is lower than that observed in the studies with EBUS-TBNA. 17 , 18 Garwood et al demonstrated that EBUS-TBNA of mediastinal/hilar lymph nodes may yield a granulomatous reaction in 85% of the patients suspicious of pulmonary sarcoidosis. 18 The presence of non-caseating granulomas on cytological examination, however, was not sufficient to diagnose sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of sarcoidosis with conventional TBNA has been reported in 48%–82% of the cases, which is lower than that observed in the studies with EBUS-TBNA. 17 , 18 Garwood et al demonstrated that EBUS-TBNA of mediastinal/hilar lymph nodes may yield a granulomatous reaction in 85% of the patients suspicious of pulmonary sarcoidosis. 18 The presence of non-caseating granulomas on cytological examination, however, was not sufficient to diagnose sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a small number of cases in this series underwent pulmonary resection after a negative VAM, there were no false negatives when the resected specimens from the routine lymphadenectomy at time of surgery were analysed. The number of patients included is small [2][3][4][5][6][7][8]. Major haemorrhagic complication requiring sternotomy is rare, but can by fatal [3].…”
Section: Commentsmentioning
confidence: 99%
“…Its sensitivity is high (75-90%) and complications are rare, although potentially severe. 5, [38][39][40][41] However, it can only reach the paratracheal stations (levels one, two and four) and the subcarinal station (level seven, anterior). 5 In general, this technique is not popular among surgeons; 42 in addition, the increasing availability and accuracy of ultrasound-guided minimally invasive techniques have been challenging the reference role of mediastinoscopy in recent years.…”
Section: Surgical Techniquesmentioning
confidence: 99%